Sintesis Zeolit 4A Dari Abu Limbah Sawit Dengan Variasi Suhu Pembentukan Gel Dan Variasi Volume Natrium Silikat Dengan Natrium Aluminat - Nur Asia; Fajril Akbar; Rozanna Sri Irianty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Zeolite 4A is one of the synthetic zeolite which it is used as ion exchange. This zeolite can be synthesized from silica and alumina. In this research, the palm ash is used as source of silica. The purpose of this research is produce the zeolite 4A by using palm ash and getting the best condition of synthesis zeolite 4A. Synthesis of zeolite 4A made by mixing sodium silicate and sodium aluminate with variation of volume at 55:45 and 60:40 mL:mL and variety of gelling temperatures are 60, 70, and 80oC with rate of agitation at 200 rpm. Then the gel formed will be heated in the oven at 80oC for 8 hours and washed it until it’s pH neutral. After that, dried it at 120oC for 3 hours. The synthesis product is analyzed by using spectrophotometry fourier transform infra red (FTIR) and X ray diffraction (XRD). The best conditions of cristalization toproduce the zeolite 4A by using palm ash are temperature at 60oC and variation of volume at 55:45 mL:mL.Keywords : palm ash, spectrophotometry ftir, xrd, zeolite 4A